Supercritical fluid extraction and encapsulation of Rivas (Rheum ribes) flower: Principal component analysis (PCA) - Seyyed Ali Hoseini; Mohsen Vazifedoost; Bahareh Hajirostamloo; Zohreh Didar; Mohamad Mehdi Nematshahi (Heliyon)
Supercritical CO2 modified by polar solvents can extract a wide variety of polar and non-polar chemical components compared to conventional methods. The current study aims to extract Rivas (Rheum ribes) flower using the ethanol modified supercritical CO2 (SCO2-EOH) method; analyze its chemical compounds and bioactivity, encapsulate the extract in maltodextrin, gum-Arabic (GA), and their combination (GA + MD) using the spray drying method and investigate the differences among microparticles using Principal Component Analysis (PCA). The Rivas extract obtained by the SCO2-EOH method was a rich source of unsaturated fatty acids (mainly linoleic acid: 57.58 %), phytosterols (mainly sitosterol: 197.02 and campesterol: 144.47 mg/100g), terpenoids (mainly camphor: 17.52 %; and 1,8-cineol: 10.91 %) and phenolics (mainly m-coumaric acid: 48.22; luteolin: 38.07 and gallic acid: 26.25 mg/g). The yield of Rivas extract was 1.62 ± 0.27 %. The extract bioactivity was as follows: antioxidant activity of 89.6 ± 1.39 %; total phenolic content of 306.19 ± 13.59 mg GAE/g; total flavonoid content of179.84 ± 5.77 mg QE/g and a comparable antimicrobial effect to synthetic antimicrobials against E. coli, L. monocytogenes, and A. fumigatus. The encapsulation efficiency of microparticles was 90.53 % for MD to 93.23 % for GA + MD (P < 0.05). The microparticles had irregular semi-spherical shapes with wrinkled surfaces. According to the PCA, MD showed the best solubility and the lowest price, making it a cost-effective ingredient to improve the nutritional-value of food formulations. If the stability of bioactive compounds is more important, GA + MD will be the best choice.